Analysis of strategic natural resources: the FEW Nexus model applied to Irpinia (Italy) and implications for regional planning - Mazzeo, Giuseppe (TeMA - Journal of Land Use, Mobility and Environment, 2023)
Natural resources are strategic resources. They are becoming increasingly important in policies combating climate change. Moreover, their protection and enhancement are fundamental for actions of sustainable development. The paper analyses specific types of natural resources (soil, water and energy) and identifies their potential contribution to local development in a perspective of reduced environmental loads. General attention to the three systems of resources is evidenced by the development of research based on the FEW Nexus model which, since the 1970s, has explored the connections existing between them, as well as the development of parallel research lines. The latter can directly impact on regional planning and bring about necessary changes in currently applied plans so as to adapt them to evolving circumstances. A case study of interest is the area of Avellino, one of the inland provinces of Campania. The paper shows that the regional planning tool for the province only partially considers such resources, failing to assign to them any strategic importance. This may be considered a weakness both in regional planning and in land management because it excludes in advance, from analyses and forecasts, resources that can make a major contribution to the sustainable economic development of the province. To this end, the last section of the paper proposes changes in regional planning policy.